Responsabilità e etica della cura tra esistenza e relazione - Miano, Francesco (Filosofia Morale/Moral Philosophy, 2024)
The essay aims to delve into the centrality of the notions of care and responsibility within an ethical framework that can move beyond the concreteness of existence, overcoming abstract and deductive forms, and activating new paths of thought. The work emphasizes, in particular, the connection between care, responsibility, and the constitutive relational dimension of the human subject. Care and responsibility bring to light the indispensability of this dimension, highlighting how human existence is inherently characterized ethically in terms of response and taking on oneself.